Selective targeting of transforming growth factor-beta1 into TCR/CD28 signalling plasma membrane domains silences T cell activation - Harder, Thomas (Cell Commun Signal, 2014)
TGFβ1 (Transforming Growth Factor-beta1) is a versatile regulator of T cell immune responses. Depending on its context in the immunological environment, TGFβ1 guides T cells toward specific activation programs including T(H)17 and regulatory T cell activities. Moreover, TGFβ signals function in immune homeostasis by directly attenuating T cell effector activities. We uncovered a novel context under which TGFβ1 stringently and reversibly silences activation responses of resting human T cells to TCR/CD28 stimulating surfaces: Using ligand-presenting beads, TGFβ1 and TCR/CD28-activating signals were directed into defined plasma membrane domains of T cells. Selective targeting of TGFβ1 cytokine into TCR/CD28 signalling plasma membrane domains held back early response of TCR-proximal tyrosine phosphorylation and bead engulfment at activation sites. Consequently, downstream induction of proliferation and cytokine secretion were stringently attenuated. After extended incubation with TGFβ1-presenting beads, silenced T cells became receptive again to activation by renewed TCR/CD28-stimuli, indicating that the unresponsive state of T cells was reverted and did not reflect long-lasting anergy or decrease in T cell viability. These findings outline a new strategy of physically linking TGFβ1 and TCR-activating functions for the treatment of disease and pathological conditions which are caused by unwanted T cell activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12964-014-0074-6) contains supplementary material, which is available to authorized users.